Pathogenesis of chronic heart failure: change of dominating paradigm - V. V. Kalyuzhin; A. T. Teplyakov; Yu. Yu. Vechersky; N. V. Ryazantsevа; A. P. Khlapov (Бюллетень сибирской медицины)
The review considers literature data reflecting the evolution of views on pathogenesis of chronic heart failure. Connection of revision of a dominating paradigm of pathogenesis at every stage of development of cardiology with changes in approaches to therapy of chronic heart failure is analyzed.